2019
DOI: 10.1080/16089677.2019.1585069
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between magnesium and lipids in patients with diabetes mellitus

Abstract: Non-communicable diseases, especially cardiovascular diseases (CVD), have become more prevalent across the world, more so in developing countries. Novel methods in the management of CVD risks in patients with diabetes mellitus, type 2 (DM2) requires constant attention and an ever-evolving approach. The role of magnesium supplementation in the management of CVD has been described, but the relationship between serum magnesium (Mg) and the lipid subsets have had conflicting results in different population groups.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
3
0
2
Order By: Relevance
“…Estos resultados contradictorios podrían deberse a diferencias en el metabolismo de los lípidos relacionadas con las etnias, lo cual se ha reportado en pacientes portadores de diabetes de Sudáfrica en quienes se determinó relación lineal positiva y significativa entre niveles de Mg y CT, así como entre Mg y LDL, pero no entre Mg y HDL y TG, aparentemente como consecuencia de menor grasa visceral que en mujeres caucásicas 34 . Aunado a esto, en población china después de ajustar a factores confusores, niveles elevados de Mg sérico fueron asociados con niveles elevados de CT, HDL, LDL y TG, como consecuencia de la afinidad del Mg por ciertos fosfolípidos 35,36 .…”
Section: Discussionunclassified
“…Estos resultados contradictorios podrían deberse a diferencias en el metabolismo de los lípidos relacionadas con las etnias, lo cual se ha reportado en pacientes portadores de diabetes de Sudáfrica en quienes se determinó relación lineal positiva y significativa entre niveles de Mg y CT, así como entre Mg y LDL, pero no entre Mg y HDL y TG, aparentemente como consecuencia de menor grasa visceral que en mujeres caucásicas 34 . Aunado a esto, en población china después de ajustar a factores confusores, niveles elevados de Mg sérico fueron asociados con niveles elevados de CT, HDL, LDL y TG, como consecuencia de la afinidad del Mg por ciertos fosfolípidos 35,36 .…”
Section: Discussionunclassified
“…Studien konnten zeigen, dass eine inverse Korrelation zwischen dem Magnesiumstatus und einzelnen Parametern des Lipidstoffwechsels besteht 24 . Magnesium erhöht die Aktivität der Lecithin-Cholesterin-Acyltransferase und der Lipoproteinlipase, die den Triglyceridspiegel senken und den HDL-Cholesterinspiegel erhöhen.…”
Section: Rolle Von Magnesium Beim Metabolischen Syndromunclassified
“…Despite the paucity of Mg studies in GDM, the supplementation of Mg during pregnancy is suggested to improve maternal and neonatal outcomes due to the beneficial effects observed in type 1 diabetes patients after oral Mg intake (Rodríguez‐Morán & Guerrero‐Romero, 2003; Veronese et al., 2016). In addition to the insulin signaling, Mg is also known to influence systemic inflammation, antioxidant parameters, and lipid profile in diabetes patients (Jansen van Vuuren et al., 2019; Kim et al., 2010; Nasri & Baradaran, 2008; Olatunji & Soladoye, 2007). However, the effect of Mg on these processes in GDM remains unclear and there seems to be no consensus among researchers regarding the use of Mg supplements in pregnant women.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in the present study, we have used a meta‐analysis of RCTs to assess the effect of Mg supplementation in GDM patients during pregnancy on (1) glycemic parameters—Fasting plasma glucose (FPG); Insulin levels; Homeostatic Model Assessment of Insulin Resistance (HOMA‐IR), (2) biomarkers of metabolic status including oxidative stress, and inflammation—Glutathione (GSH), Total antioxidant capacity (TAC), (3) Inflammation biomarker—C‐reactive protein (CRP). These markers are chosen on the basis of previous literature reports that have established a relationship between GDM pathogenesis and the level of these markers (Alptekin et al., 2016; Jansen van Vuuren et al., 2019; Kim et al., 2010; Nasri & Baradaran, 2008; Olatunji & Soladoye, 2007; Zhu et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation